Proceedings of the 30th European Solid-State Circuits Conference (IEEE Cat. No.04EX850)
DOI: 10.1109/essder.2004.1356543
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of embedded SONOS memories

Abstract: In this work, arrays of two transistor (2T) and compact SONOS memory cells are presented together with an extensive reliability investigation. SONOS, which acronym stands f o r semiconductor-oxide-nitride-oxidesemiconductor, is a non-volatile memory concept, which has recently regained strong attention because floating gate flash reaches its scaling limits. The better scaling perspective together with the ease of inregration in a base line CMOS process makes SONOS an excellent candidate for embedded flash in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This is mainly due to the "poor" quality of the so-called default devices used for comparison (stoichiometric nitride). We obtained the best overall results with "standard" nitride [43], [44]. A stoichiometric Si N layer, formed with precursors SiH Cl (DiChloroSilane (DCS)) and NH , showed the best compromise between program/erase efficiency and reliability.…”
Section: B Sonos Memory Fabricationmentioning
confidence: 83%
See 4 more Smart Citations
“…This is mainly due to the "poor" quality of the so-called default devices used for comparison (stoichiometric nitride). We obtained the best overall results with "standard" nitride [43], [44]. A stoichiometric Si N layer, formed with precursors SiH Cl (DiChloroSilane (DCS)) and NH , showed the best compromise between program/erase efficiency and reliability.…”
Section: B Sonos Memory Fabricationmentioning
confidence: 83%
“…Concerning SONOS memories, it has been shown that a programming window well exceeding 2 V (in combination with a narrow distribution: mV) can be achieved using low program voltages (down to 11 V) and P/E times in the order of 1-100 ms [43], [44]. The erase saturation phenomenon (at high /long ), which could cause device degradation, has been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations